Analisis Kerangka Hukum Ahli Waris Pengganti dalam Perkara Kewarisan Islam: Perspektif Pengadilan Tinggi Agama DKI Jakarta - Budiono, Eko; Mukhlas, Oyo Sunaryo; Mustofa, Mustofa; Solehudin, Ending; Ridwan, Ahmad Hasan (Syariah: Jurnal Hukum dan Pemikiran, 2023)
The purpose of this study is to comprehensively analyze the construction and legal certainty of replacement heirs in the compilation of Islamic law and its application in the religious courts of the DKI Jakarta region. This research uses a qualitative method with a normative legal approach, legislation, decision analysis, and Islamic law literature. Primary sources are obtained from the decisions of the religious courts of the DKI Jakarta high religious court region numbered: 131/pdt.p/2022/pa.jp, 339/pdt.p/2021/pa.jp, 166/pdt.p/2021/pa-jb, 3950/pdt.g/2020/pa-js, the compilation of Islamic law, and other legal materials related to inheritance. Meanwhile, secondary sources are obtained from literature searches such as books, documents, and journals that have the same relevance as this research. After the data is obtained and collected, data will be filtered and grouped according to its type, then the data is analyzed using descriptive analysis to be able to provide an overview of the existing problems. The results showed that, the legal construction of the concept of substitute heirs in the Compilation of Islamic Law in the Religious Courts in the DKI Jakarta PTA region by placing the position of substitute heirs by applying justice to the inheritance of his parents who had died before the heir. The research confirms the legal construction and rationale behind substitute heirs in Islamic inheritance law, highlighting their significance in inheritance disputes. Recognized under KHI Article 185, substitute heirs play a crucial role in ensuring fairness and equity in inheritance distribution. However, obstacles such as public awareness, evidentiary challenges, and conflicts with local customs impede the effective implementation of the substitute heir rule.